Territorial jurisdiction of the International Criminal Court - Vagias, Michail (cambridge, 2014)
"There are many variables of territoriality available to national courts under contemporary international law. Does the same apply to the International Criminal Court? And if so, what are the limits to the teleological expansion of the Court's territorial jurisdiction as regards, for example, partial commission of a crime in State not Party territory, crimes committed over the internet or crimes committed in occupied territories? Michael Vagias's analysis of the law and procedure surrounding the territorial jurisdiction of the Court examines issues such as the application of localisation theories of territoriality and the means of interpretation for article 12(2)(a); the principle of legality (nullum crimen sine lege) and human rights law for the interpretation of jurisdictional provisions; compe;tence de la compe;tence; crimes committed over the internet; and the procedure for jurisdictional objections"--